The research objective was to study tree's vegetation structure based on diameter class distribution on varians vegetation types at Salak Mountain. Samples were taken at north, south, east, and west facing slope of Salak Mountain using line transect. Systematic sampling with random start was used to locate the transetcs. Measuring stem diameter at breast height was done in order to study the tree diameter class distribution. Non parametric U Man Whitney statistic was used to know whethe - Muhammad Wiharto; Cecep Kusmana; Lilik Budi Prasetyo; Tukirin Partomihardjo (Forum Pasca Sarjana, 2009)
The research objective was to study tree's vegetation structure based on diameter class distribution on varians vegetation types at Salak Mountain. Samples were taken at north, south, east, and west facing slope of Salak Mountain using line transect. Systematic sampling with random start was used to locate the transetcs. Measuring stem diameter at breast height was done in order to study the tree diameter class distribution. Non parametric U Man Whitney statistic was used to know whether there was a different in number of individual at all diameter class in each vegetation type. At mix forest and plantation forest, the tree diameter class distribution forming J curve shape. At bamboo forest, the individual number increase at the highest class diameter. The number of individual trees were highest at mix forest and lowest at bamboo forest. Key words: Mount Salak, Reverse J Curve, tree diameter class, vegetation type